Dari Individu Ke Kolaboratif: Transformasi Budaya Sekolah Untuk Kesuksesan Kurikulum Merdeka - Indra Joni, Yoyon; somantri, Manap; Putri Kartiwi, Asti (Manajer Pendididikan, 2025)
This study aims to describe the implementation of a collaborative culture in the planning, implementation, and evaluation of learning as well as to identify its challenges in the curriculum implementation at SMA Negeri 1 Bengkulu Selatan by employing a qualitative descriptive approach through interviews, observations, and document analysis, with participants consisting of the principal, vice principal for curriculum, teachers, and students. The findings reveal that a collaborative culture is integrated into the planning, implementation, and evaluation of learning, characterized by effective interaction, open communication, participatory leadership, and collective problem-solving that support the creation of student-centered learning. Nevertheless, the implementation of a collaborative culture faces challenges such as limited time, differences in perception, individualistic tendencies, difficulties in adapting to change, low participation, and high administrative workload. This study offers novelty by uncovering the dynamics of collaboration at the school level through the perspectives of various stakeholders, emphasizing the importance of institutional support and strengthening a collaborative work culture as strategies to enhance the effectiveness of curriculum implementation, while also contributing to the literature on collaboration-based curriculum implementation and providing practical implications for schools in building a sustainable collaborative culture.